Persepsi Kualitas vs. Pemasaran Media Sosial: Memahami Efek Berbeda pada Kepercayaan Merek dan Loyalitas Merek - Ratna Nabila Permataningrum; Amelindha Vania (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This study aims to examine the effect of Social Media Marketing and Perceived Quality on Brand Loyalty with Brand Trust as an intervening variable. This study was conducted on Facetology consumers in the TikTok application in five districts in Malang City. The research method uses a quantitative approach with data collection through questionnaires distributed online through google forms to Facetology consumers. The measurement scale in this study is using a Likert scale. The sampling technique used was non probability sampling technique with purposive sampling method with a sample size of 110 respondents. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 3 software to test the relationship between variables. The results showed that Social Media Marketing has no influence on brand trust. Perceived Quality has a significant effect on Brand Loyalty. Brand Trust is proven to have a positive and significant influence iton brand loyalty. The results of this study are expected to provide insight for business people, especially for marketers who are engaged in the beauty industry and use social media platforms such as TikTok to market their products. By understanding these dynamics, businesses can refine their marketing strategies to enhance brand loyalty among consumers, ultimately leading to stronger customer relationships and increased sales